Housing market filtering in the Oslo region: pro-market housing policies in a Nordic welfare-state context. Issue 4 (2nd October 2019) - Turner, Lena Magnusson; Wessel, Terje
Abstract: Vacancy chain theory suggests that mobility opportunities spread within and between specific states, typically flowing from attractive to less attractive units, with households moving in the opposite direction. We explore whether such welfare gains apply in a context, the Oslo region, which combines egalitarian welfare programmes and pro-market housing policies. We use merged census and register data from 2011, and include all events that initiate vacancies. Our results show that rental submarkets function poorly. There are many vacancies, but most of them are immediately absorbed by recruits, that is, households who leave no vacancy behind. Opportunities for disadvantaged groups are further reduced by rapid absorption of owner-occupied flats, often because privileged nest-leavers eschew the rental markets. Two related outcomes are segmentation between submarkets and segregation between Oslo Outer East and the remaining city. All of these adverse consequences reflect the costs of current policies, and call for initiatives that increase and improve opportunities in the rental sector.